Effectiveness of Using Warm Water to Reduce Primary Dysmenorrhea Pain Intensity in Grade X Female Students - Susilawati, Susilawati; Halimatusyadih, Leni; Fairuza, Filda; Janah, Euis Nida Farhatul (Jurnal Biologi Tropis, 2024)
The maturation of sexual organs for reproduction marks the beginning of the adolescent phase, which is a crucial stage in human development. The onset of menstruation is a sign of reproductive organ maturity in female adolescents (Menarche). The purpose of this study was to determine the effectiveness of using warm water compresses on the intensity of reducing primary dysmenorrhea in grade X female students. A sample of sixty respondents was used in this quasi-experimental study, which utilized a one-group, one-test, and one-control design. The Wilcoxon test was used to conduct an analysis and observation sheets were used to collect data. The study's findings had a p-value of 0.000 < 0.05, which was significantly lower than the significant result of 5%, therefore the conclusion is that Ha is accepted, which means that there is an effectiveness of using warm water compresses on reducing pain intensity during primary dysmenorrhea in grade X female students at SMAN2 Rangkabitung in 2024. The conclusion is that the intensity of primary dysmenorrhea pain can be eliminated with warm water compresses.